Participation of heparin binding proteins from the surface of Leishmania (Viannia) braziliensis promastigotes in the adhesion of parasites to Lutzomyia longipalpis cells (Lulo) in vitro (2012)
Background: Leishmania (V.) braziliensis is a causative agent of cutaneous leishmaniasis in Brazil. During the parasite life cycle, the promastigotes adhere to the gut of sandflies, to avoid being eliminated with the dejection. The Lulo cell line, derived from Lutzomyia longipalpis (Diptera: Psychodidae), is a suitable in vitro study model to understand the features of parasite adhesion. Here, we analyze the role of glycosaminoglycans (GAGs) from Lulo cells and proteins from the parasites in this event. Methods: Flagellar (F f) and membrane (Mf) fractions from promastigotes were obtained by differential centrifugation and the purity of fractions confirmed by western blot assays, using specific antibodies for cellular compartments. Heparin-binding proteins (HBP) were isolated from both fractions using a HiTrap-Heparin column. In addition, binding of promastigotes to Lulo cells or to a heparin-coated surface was assessed by inhibition assays or surface plasmon resonance (SPR) analysis. Results: The success of promastigotes subcellular fractionation led to the obtainment of Ff and Mf proteins, both of which presented two main protein bands (65.0 and 55.0kDa) with affinity to heparin. The contribution of HBPs in the adherence of promastigotes to Lulo cells was assessed through competition assays, using HS or the purified HBPs fractions. All tested samples presented a measurable inhibition rate when compared to control adhesion rate (17 ± 2.0% of culture cells with adhered parasites): 30% (for HS 20?g/ml) and 16% (for HS 10μg/ml); HBP Mf (35.2% for 10μg/ml and 25.4% for 20μg/ml) and HBP Ff (10.0% for 10μg/ml and 31.4% for 20μg/ml). Additionally, to verify the presence of sulfated GAGs in Lulo cells surface and intracellular compartment, metabolic labeling with radioactive sulfate was performed, indicating the presence of an HS and chondroitin sulfate in both cell sections. The SPR analysis performed further confirmed the presence of GAGs ligands on L. (V.) braziliensis promastigote surfaces. Conclusions: The data presented here point to evidences that HBPs present on the surface of L. (V.) braziliensis promastigotes participate in adhesion of these parasites to Lulo cells through HS participation. © 2012 de Castro Crtes et al.; licensee BioMed Central Ltd.